2020
DOI: 10.3390/ijms21113882
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Single- and Double-Strand DNA Breaks in Human Spermatozoa on Assisted Reproduction

Abstract: Several cellular insults can result in sperm DNA fragmentation either on one or both DNA strands. Oxidative damage, premature interruption of the apoptotic process and defects in DNA compaction during spermatogenesis are the main mechanisms that cause DNA breaks in sperm. The two-tailed Comet assay is the only technique that can differentiate single- (SSBs) from double- (DSBs) strand DNA breaks. Increased levels of the phosphorylated isoform of the H2AX histone are directly correlated with DSBs and proposed as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 74 publications
0
49
0
1
Order By: Relevance
“…However, this variability in results could be partly due to the different origin and types of DNA strand breaks in sperm. In this sense, abortive apoptosis mainly originates from DNA double-strand breaks in sperm [ 11 ], and this type of DNA fragmentation is associated with an increase in miscarriage risk [ 35 ]. As the MACS procedure is based on the selective elimination of apoptotic cells, the sperm population isolated after this sperm-selection technique presumably had a significant reduction in sperm containing double-strand breaks and thereby reduced the chance that one of these spermatozoa would be selected for ICSI cycles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this variability in results could be partly due to the different origin and types of DNA strand breaks in sperm. In this sense, abortive apoptosis mainly originates from DNA double-strand breaks in sperm [ 11 ], and this type of DNA fragmentation is associated with an increase in miscarriage risk [ 35 ]. As the MACS procedure is based on the selective elimination of apoptotic cells, the sperm population isolated after this sperm-selection technique presumably had a significant reduction in sperm containing double-strand breaks and thereby reduced the chance that one of these spermatozoa would be selected for ICSI cycles.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptotic mechanisms induce the activation of nuclear endonucleases that lead to the generation of double-strand breaks (DSBs) on sperm DNA. These are closely related with implantation failures and miscarriage [ 11 ]. Sertoli cells are able to distinguish and eliminate those sperm cells with apoptotic markers on the outer plasma membrane, such as phosphatidylserine (PS) residues.…”
Section: Introductionmentioning
confidence: 99%
“…As possible explanations for this situation, we suggest the following hypotheses: (1) PIO may increase the formation of DNA DSBs while it cannot induce SSBs. Some agents such as oxidative stress can damage both DNA SSBs and DSBs, whereas defective chromatin condensation and the induction of abortive apoptosis can result in the generation of DNA DSBs (Agarwal et al ., 2020). (2) DNA SSBs may convert into DNA DSBs in bladder cells treated with PIO.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, recent studies using Comet assay provide information about different types of DNA breaks (single- and double-stranded). This distinction is important since our previous studies demonstrated that single stranded DNA damage is caused by oxidative stress and to the capacity of achieving a natural pregnancy, while double stranded DNA breaks are enzymatic and related to a higher risk of recurrent miscarriage [ 8 , 39 ]. In this sense, the DNA damage data obtained for the donors and patients included in the present study fit the specific profiles of single- and double-stranded DNA breaks defined previously [ 40 ].…”
Section: Discussionmentioning
confidence: 99%